2020
DOI: 10.1002/cam4.3213
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Epstein‐Barr virus nuclear antigen 1 favor Tregs accumulation in nasopharyngeal carcinoma

Abstract: Epstein-Barr virus (EBV) is an oncogenic virus that is closely associated with development of several malignancies, including Hodgkin lymphoma (HL), Burkitt lymphoma, nasopharyngeal carcinoma (NPC), and EBV+ gastric carcinoma (GC). EBV-DNA can be detected in approximately 90% of NPC tissues, where the virus express a limited subset of genes; these include EBV nuclear antigen 1 (EBNA1), latent membrane protein 1 (LMP1), and LMP2. Although massive EBV-specific cytotoxic T cells (CTLs) can be detected in NPC, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 26 publications
(31 reference statements)
0
33
0
Order By: Relevance
“… 4 We have previously demonstrated that EBV-EBNA1 promotes the production of Treg cells in a TGFβ1-dependent manner. 14 However, the role and specific mechanism of EBV-EBNA1 in chemoattraction of Treg cells remains poorly understood. The present study is the first to demonstrate that EBV-EBNA1 regulates chemotactic migration of Treg cells via the TGFβ1-SMAD3-PI3K-AKT-c-JUN-miR-200a-CXCL12-CXCR4 feedback loop to create an extremely immunosuppressive microenvironment in NPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 We have previously demonstrated that EBV-EBNA1 promotes the production of Treg cells in a TGFβ1-dependent manner. 14 However, the role and specific mechanism of EBV-EBNA1 in chemoattraction of Treg cells remains poorly understood. The present study is the first to demonstrate that EBV-EBNA1 regulates chemotactic migration of Treg cells via the TGFβ1-SMAD3-PI3K-AKT-c-JUN-miR-200a-CXCL12-CXCR4 feedback loop to create an extremely immunosuppressive microenvironment in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, EBV-EBNA1-positive NPC cells were shown to convert naïve T cells into Treg cells by upregulation of TGFβ1 in vitro. 14 Hence, we speculated that TGFβ1 plays certain roles in the production of Treg cells and probably in chemotactic migration of Treg cells in EBV-EBNA1positive NPC microenvironment. The initial results of in vitro migration assay of Treg cells and western blot analysis indicated that the culture supernatant of EBNA1positive NPC cells promotes the tropism and migration of Treg cells compared with that in the EBNA1-negative groups; however, SB431542 (a specific inhibitor of type I TGFβ receptor kinase) blocked the expression of TGFβ1 induced by EBNA1 and reversed the migration of Treg cells driven by EBNA1 (figure 1A,B, (online supplemental figure 1A).…”
Section: Ebv-ebna1 Promotes Chemotactic Migration Of Treg Cells By Activating Tgfβ1-smad3 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the frequency of γδ T cells in patients with EBV-positive NPC was unaltered but showed an impaired T-cell function characterized by reduced cytotoxicity for the NPC targets [156]. In addition, a higher frequency of Tregs was shown in some EBV-associated malignancies [157][158][159][160], while Tregs are only poorly represented in BL [145]. Tregs are potent suppressors of other immune cells and can create an immunosuppressive environment [160].…”
Section: Cellular Composition Of the Tmementioning
confidence: 99%
“…In addition, a higher frequency of Tregs was shown in some EBV-associated malignancies [157][158][159][160], while Tregs are only poorly represented in BL [145]. Tregs are potent suppressors of other immune cells and can create an immunosuppressive environment [160]. In some EBV-positive malignancies, lower frequencies of CD8 + T cells as well as of other effector immune cells, such as NK cells and M1 macrophages, were found [158,160].…”
Section: Cellular Composition Of the Tmementioning
confidence: 99%